2016
DOI: 10.1093/hsw/hlw040
|View full text |Cite
|
Sign up to set email alerts
|

Talking about Sexuality and Intimacy with Women Spousal Caregivers: Perspectives of Service Providers

Abstract: This article reports the findings of an exploratory study examining service provider perceptions and experiences of addressing sexuality and intimacy with women spousal caregivers. The caregiver-provider encounter is examined, and challenges faced by service providers in addressing sexuality are considered. Themes identified include ambivalence and discomfort, personal and institutional barriers, meanings attributed to sexuality and intimacy, and lack of opportunities to discuss experiences. Strategies to over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Given the importance of sexual and emotional intimacy for quality of life in ageing and care-giving (Davies et al , 2012; Roelofs et al , 2017), it is noteworthy that the findings did not reveal any evidence of discussions with external support providers around intimacy. It could be suggested that not only are male care-givers unlikely to ask for support around spousal intimacy, due to their ‘independent’ approach to care-giving (Hong and Coogle, 2014), but that external support providers are hesitant to offer support in this area (Brotman et al , 2016; Haesler et al , 2016). Finally, findings from the current study indicated that future support for spousal male care-givers should consider a tailored approach which includes recognition of gender as a factor in coping, and acknowledges that support for older male care-givers should align with dominant masculine norms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the importance of sexual and emotional intimacy for quality of life in ageing and care-giving (Davies et al , 2012; Roelofs et al , 2017), it is noteworthy that the findings did not reveal any evidence of discussions with external support providers around intimacy. It could be suggested that not only are male care-givers unlikely to ask for support around spousal intimacy, due to their ‘independent’ approach to care-giving (Hong and Coogle, 2014), but that external support providers are hesitant to offer support in this area (Brotman et al , 2016; Haesler et al , 2016). Finally, findings from the current study indicated that future support for spousal male care-givers should consider a tailored approach which includes recognition of gender as a factor in coping, and acknowledges that support for older male care-givers should align with dominant masculine norms.…”
Section: Resultsmentioning
confidence: 99%
“…There is also evidence to suggest that female health-care staff have less-permissible attitudes in their evaluation of sexual appropriateness than their male counterparts (Haesler et al , 2016). Brotman et al (2016) go further to point out that the age and gender of health-care professionals affected their comfort levels in this area, and that although staff understood the importance of discussing sexuality, they often felt ‘awkward’ about raising such a personal issue or assumed that it was not a priority for the care-giver. Findings such as these would be particularly important to consider in planning future support for male care-givers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation